TLR4 Signaling by Heme and the Role of Heme-Binding Blood Proteins - Janciauskiene, Sabina; Vijayan, Vijith; Immenschuh, Stephan (Frontiers in Immunology, 2020)
Toll-like receptors (TLRs), also known as pattern recognition receptors, respond to exogenous pathogens and to intrinsic danger signals released from damaged cells and tissues. More recently, heme has been suggested as an agonist for TLR4, the receptor for the pro-inflammatory bacterial lipopolysaccharide (LPS). Heme is a double-edged sword with contradictory functions. On the one hand, heme has vital cellular functions as the prosthetic group of hemoproteins such as hemoglobin, myoglobin and cytochromes. On the other hand, if released from destabilized hemoproteins, free, non-protein bound heme can have pro-oxidant and pro-inflammatory effects. Mechanisms contributing to heme induced generation of reactive oxygen species, activation and/ or death of cells are not fully understood. In this review, the complex interactions between heme and TLR4 are critically discussed with a particular focus on the role of heme-binding serum proteins in handling extracellular heme and its impact on TLR4 signaling. Finally, the role of heme as an indirect trigger of TLR4 activation and species-specific differences in the regulation of heme-dependent TLR4 signaling are highlighted.